Vaccines to prevent leishmaniasis. Issue 3 (14th March 2014) - Kumar, Rajiv; Engwerda, Christian
Abstract : Leishmaniasis is a parasitic disease that encompasses a range of clinical manifestations affecting people in tropical and subtropical regions of the world. Epidemiological and experimental data indicate that protection from disease can be achieved in most people. In addition, we know how the host immune system must respond to infection in order to control parasite growth. However, there is still no vaccine for use in humans. Here, we review our understanding of host immunity following Leishmania infection and also discuss recent advances in the development of vaccines to prevent leishmaniasis, highlighting a new promising approach that targets the parasite hemoglobin receptor.